Synthetic hospital wastewater treatment by coupling submerged membrane bioreactor and electrochemical advanced oxidation process: Kinetic study and toxicity assessment. (February 2018) - Ouarda, Yassine; Tiwari, Bhagyashree; Azaïs, Antonin; Vaudreuil, Marc-Antoine; Ndiaye, Sokhna Dieng; Drogui, Patrick; Tyagi, Rajeshwhar Dayal; Sauvé, Sébastien; Desrosiers, Mélanie; Buelna, Gerardo; Dubé, Rino
Abstract: In this work, the combination of membrane bioreactor (MBR) and electro-oxidation (EO) process was studied for the treatment of a synthetic hospital wastewater fortified with four pharmaceutical pollutants namely carbamazepine (CBZ), ibuprofen (IBU), estradiol (E-E) at a concentration of 10 μg L −1 venlafaxine (VEN) at 0.2 μg L −1 . Two treatment configurations were studied: EO process as pre-treatment and post-treatment. Wastewater treatment with MBR alone shows high removal percentages of IBU and E-E (∼90%). Unlikely for CBZ and VEN, a low elimination percentage (∼10%) was observed. The hydraulic and the solid retention times (HRT and SRT) were 18 h and 140 d respectively, while the biomass concentration in the MBR was 16.5 g L −1 . To enhance pharmaceuticals elimination, an EO pretreatment was conducted during 40 min at 2 A. This configuration allowed a 92% removal for VEN, which was far greater than both treatments alone, with lower than 30% and 50% for MBR and EO, respectively. The MBR-EO coupling (EO as post-treatment) allows high removal percentages (∼97%) of the four pharmaceutical pollutants after 40 min of treatment at a current intensity of 0.5 A with Nb/BDD as electrodes. This configuration appears to be very effective compared to the first configuration (EO-MBR) where EO process is used as a pre-treatment. Toxicity assessment showed that the treated effluent of this configuration is not toxic to Daphnia magna except at 100% v/v. The MBR-EO coupling appears to be a promising treatment for contaminated hospital effluents. Highlights: MBR alone shows elimination of biodegradable pollutant only. EO – MBR coupling does not allow an elimination of all the micropollutants. MBR followed by EO treatment is efficient on the four selected model contaminants. MBR – EO coupling generates a non-toxic effluent to Daphnia magna.